Nanoengineering of cathode layers for solid oxide fuel cells to achieve superior power densities - Katherine Develos-Bagarinao (Nature Portfolio, 2021)
High-performance cathode materials are crucial for the development of solid oxide fuel cells. Here, the authors present a nanoengineering approach to boost cathode performance in conventional anode-supported cells, demonstrating a viable route to attaining higher power output.